Implementing Sustainable and Innovative Renewable Energy at Universiti Sains Islam Malaysia - Zuhairuse Md Darus; Yakubu Aminu Dodo; Nasrudin Sharkawi (Universiti Kebangsaan Malaysia, 2024)
Proceedings of Conference on Regional Architecture and Built Environment 2018 (SeniBINA2018) ‘Theme: National Architectural Identity’, Palm Garden Hotel Putrajaya, 13 – 14 November 2018.